2006
DOI: 10.1111/j.1440-172x.2006.00553.x
|View full text |Cite
|
Sign up to set email alerts
|

Needlestick and sharps injuries among nurses in a tropical Australian hospital

Abstract: Although needlestick and sharps injuries (NSI) represent a major hazard in nursing practice, most studies rely on officially reported data and none have yet been undertaken in tropical environments. Therefore, we conducted a cross-sectional NSI survey targeting all nurses within a tropical Australian hospital, regardless of whether they had experienced an NSI or not. Our overall response rate was 76.7%. A total of 39 nurses reported 43 NSI events in the previous 12 months. The most common causative device was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 16 publications
3
41
2
Order By: Relevance
“…Similar to Japan, research from Turkey 9) , Australia 35) , Singapore 45) , Taiwan 33) , Saudi Arabia 46) and Korea 12) has indicated that disposable syringes and medication ampoules continue to present NSI risks for HCW. Butterfly needles were also a reasonably common cause of NSI in the current study, although this is not surprising, because butterfly needles are used much more frequently for blood drawing and IV infusion in Japan, than in other countries such as the US 44) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to Japan, research from Turkey 9) , Australia 35) , Singapore 45) , Taiwan 33) , Saudi Arabia 46) and Korea 12) has indicated that disposable syringes and medication ampoules continue to present NSI risks for HCW. Butterfly needles were also a reasonably common cause of NSI in the current study, although this is not surprising, because butterfly needles are used much more frequently for blood drawing and IV infusion in Japan, than in other countries such as the US 44) .…”
Section: Discussionmentioning
confidence: 99%
“…Questions focussed on work support, mental pressure, time pressure, work responsibility and many others. NSI questions were based on similar research previously conducted across a variety of countries [33][34][35] . Questions focussed on the type of device which caused the injury, the number of times nurses had received such an injury in the previous 12-month, whether the item had been used on a patient prior to injury and whether nurses had officially reported to management any NSI they sustained.…”
Section: Methodsmentioning
confidence: 99%
“…Most reported sharps injuries involve nursing staff, laboratory staff, physicians, housekeepers, and other HCW. 8 World Health Organization report showed that 16,000 HCV, 66,000 HBV & 1000 HIV may have occurred worldwide. 9 The annual estimated proportion of HCW exposed to blood born pathogen globally were 2.6% for HCV, 5.9 % for HBV, and 0.5 % for HIV.…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that sharp injuries were higher among female nurses (P=0.025). In other studies, there was no significant association between injury and gender (Haddadi, Afhami & Karbakhsh 2007;Smith et al 2006b;Bijani, Sotudeh Manesh & Mohammadi 2011). The causes of injuries in female forces are due to their lower physical ability, fatigue, anxiety, stress of work, and loss of concentration.…”
Section: Discussionmentioning
confidence: 99%
“…In the studies of Smith et al (2006b) and Martins et al (2012), a few staffs did not report sharp injuries because of unawareness, insignificance of injury cases, or the fear of being accused of having no clinical skill. In our study, many staffs reported injury cases due to the high cause of informing authorities, holding at-service training, and preventive or prophylaxis treatments.…”
Section: Discussionmentioning
confidence: 99%